Japan-China 2008 Agreement: Common-Pool Resource Governance Problem - Rafyoga Jehan Pratama Irsadanar; Kan Kimura (Jurnal Studi Pemerintahan, 2021)
This research aims to answer the reason behind the stalled progress of dispute settlement in East China Sea between Japan and China, despite a high initial commitment to cooperate under "2008 Japan-China Agreement on Cooperation for the Development of East China Sea Resources" framework. This research was done qualitatively by amassing reliable literatures and relevant official documents. In accomplishing the research objective, this article employs common-pool resource (CPR) and security dilemma concepts to analyze the collected data. This research finds that the reason why the 2008 Agreement, which intended to make East China Sea as common-pool resource for Japan and China, did not work is due to the lack of institutional supply and commitment. The insufficient institutional supply was occurred since Japan and China, as appropriators of the CPR, were seeking less binding and more flexible rules. Even though that maximum result could be attained through high commitment, both Japan and China were not assured about each other intentions. Thus, the cooperation is stalled.